DIDACTIC METHODS OF FORMING A CULTURE OF COMMUNICATION AMONG SCHOOLCHILDREN (Scientific journal of the Fergana State University, 2023)
This article discusses the formation of a communication culture among students and its didactic methods. The results of the study of existing theoretical approaches indicate that the pedagogical foundations of the formation of a culture of communication among students of grades 5-9 of Uzbek schools have not been studied separately. The purpose of the study: to reveal the didactic possibilities of forming a communication culture among students. Research methods: questionnaire, question-answer, conversation, observation, analysis, analytical review, pedagogical experiment. As a result of the research, a consistent system of practical tools has been developed that contribute to the formation of a culture of communication. The socio-didactic features of the formation of the culture of communication of students are shown.